WATER QUALITY AND TROPHIC STATUS IN JATIBARANG RESERVOIR, SEMARANG - Rahmawati, Silviana Dian; Ain, Churun; Sabdaningsih, Aninditia (Fakultas Perikanan dan Ilmu Kelautan, Universitas Diponegoro, 2023)
Jatibarang Reservoir is one of the reservoirs in Central Java. This reservoir has functions for fisheries and tourism activities. The reservoir needs to be managed properly with water quality and water fertility for the function of the reservoir. The characteristics of a reservoir that is lentic cause nutrient mixing, so it is possible that there are differences in characteristics in certain columns. The purpose of this research is to analyze the water quality and trophic status in Jatibarang Reservoir. The sampling technique used purposive sampling technique at 7 stations with 3 depth points (surface, middle, and bottom). Water quality variables measured included nitrate, phosphate, and total bacteria. The results of the variable concentrations were then calculated and compared with the literature. The results showed nitrate concentrations of 0,5 – 3,5 mg/l. Phosphate results ranged from 0,29 – 2,63 mg/l. Total bacteria ranged from 2 x 102 to 1,4 x 104 CFU/ml. Based on the nitrate concentration, Jatibarang Reservoir waters are classified as oligotrophic-mesotrophic.